ANALISIS MANAJEMEN KELAS DAN IMPLIKASINYA TERHADAP HASIL BELAJAR MATEMATIKA DI MTSN 9 BANTUL - Noor Shofiyati; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Classroom management is an effort directed by the teacher to create an effective and fun teaching and learning atmosphere and can motivate students to study well according to their abilities. The purpose of this study was to analyze the classroom management of mathematics teachers at MTsN 9 Bantul and its implications for mathematics learning outcomes. This research is a case study research with a qualitative approach. Data collection techniques in this study were interviews, observation, and documentation. The data analysis technique used is descriptive qualitative analysis which includes three stages: data reduction, data display, and verification. The results showed that the teacher had created the right learning climate, managed the study space well, managed teaching and learning interactions with the right strategies, models, and methods. The supporting factor is that the teacher has skills in class management so that it has implications for mathematics learning outcomes. The inhibiting factor is that students are less aware of their obligations in terms of class discipline and cleanliness.